2023
DOI: 10.1108/jaee-10-2021-0308
|View full text |Cite
|
Sign up to set email alerts
|

SME owners and accountants' perceptions of financial information in small- and medium-sized entities: a Sri Lanka case study

Abstract: PurposeThis paper aims to examine the perceptions of owners and accountants of small- and medium-sized entities (SMEs) on the users and their financial information needs of SME financial reporting.Design/methodology/approachPostal questionnaire surveys with owners and accountants of SMEs were used to identify users and their financial information needs. In total, 1,498 questionnaires were sent to SME owners and accountants. A total of 358 questionnaires were returned, generating 323 useable questionnaires. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Entity theory emphasizes the concept of management and responsibility, where businesses are concerned with the level of business continuity and financial information for equity owners' businesses to fulfill legal needs, maintain good relations with equity holders, and hopefully be able to obtain funds in the future. (Wijekoon, Sharma, and Samkin 2023). It can be concluded that there is a separation between the company's interests and the owner's interests.…”
Section: Entity Theorymentioning
confidence: 99%
“…Entity theory emphasizes the concept of management and responsibility, where businesses are concerned with the level of business continuity and financial information for equity owners' businesses to fulfill legal needs, maintain good relations with equity holders, and hopefully be able to obtain funds in the future. (Wijekoon, Sharma, and Samkin 2023). It can be concluded that there is a separation between the company's interests and the owner's interests.…”
Section: Entity Theorymentioning
confidence: 99%
“…Financial reports play a crucial role in assessing the financial and operational health of a business (Baker & Persson, 2021;Wijekoon et al, 2023). These reports aid in identifying opportunities and challenges for improving business performance, making them a serious concern for both academic research and community service initiatives (Fonseka et al, 2022;Hastuti, 2022;Nurunnabi, 2021;Rohman & Arifin, 2020).…”
Section: Introductionmentioning
confidence: 99%